Evaluation of Reliability and Validity of Three Common Dry Eye Questionnaires in Chinese - Fan Lu; Aizhu Tao; Yinu Hu; Weiwei Tao; Ping Lu (Journal of Ophthalmology)
Purpose. To investigate the psychometric properties of three commonly used dry eye questionnaires including McMonnies Questionnaire (MQ), the Ocular Surface Disease Index (OSDI), and the Salisbury Eye Evaluation Questionnaire (SEEQ) in Chinese. Methods. This prospective cross-sectional study was conducted at the Eye Hospital of Wenzhou Medical University. Ninety-eight participants completed three questionnaires in a random order. Ophthalmic examinations including tear break-up time, corneal fluorescein staining score, and Schirmer I test were performed. Reliability, validity, and accuracy were assessed for three questionnaires. Results. There were 35 mild-to-moderate dry eye patients, 14 severe dry eye patients, and 49 non-dry eye patients. The Cronbach α of MQ, OSDI, and SEEQ was 0.54, 0.74, and 0.76, respectively, and the intraclass correlation coefficients were 0.91, 0.90, and 0.94, respectively. There were significant differences (P<0.05) in MQ and OSDI scores among different groups, but there were no statistically significant differences between the mild-to-moderate group and the severe group in terms of SEEQ scores. With cutoff values for abnormal MQ of 15, OSDI of 27.2, and SEED of 1, respectively, good dry eye diagnostic accuracies were obtained. Conclusions. The three questionnaires showed fair accuracy in the diagnosis of dry eye. The cutoff values of OSDI changed when applied to Chinese people.